The Role of Geographical Factors in the Investigation - Mátyás, Szabolcs (Magyar Rendészet, 2025)
Criminal geography in Hungary is a field of science that is researched by few people despite the fact that the research results can be used in practice. In Western Europe and North America, research results are widely used in everyday police work. Moreover, in Germany, all criminology books contain a chapter on criminal geography. This paper aims to examine the impact of geographical factors on investigative processes, focusing on how location, terrain and accessibility influence crime scene investigations and evidence collection. The author gathered factors that may influence investigations from both previous sources and his own research. The present study not only presents the role of geographical factors in the investigation but also highlights their practical implications. It lists the physical and social geographical factors that can affect crime. When presenting the factors, specific criminal cases are described where geographic knowledge was necessary during the investigation. It was this specialised knowledge that led investigators to the perpetrator. The author is confident that, based on the practical examples, more and more people in Hungary will recognise the importance and practical applicability of this field of science.